Impark : Aktuelle Kunst im Olympiapark München. - Fuchs, Martina; Huber, Thomas; Neumeister, Andreas; Schwenk, Bernhart (Frankfurt am Main : Revolver Archiv für aktuelle Kunst Frankfurt am Main, 2003)
Brockmann, Elisabeth ; Denis, Marie ; Dopfer, Afra Susanne ; Eberstadt, Stefan ; Fishkin, Vadim ; Föttinger, Claus ; Fritsch, Stephan ; Fuchs, Odile ; Hauser, Tobias ; Hüppi, Thaddäus ; Kern, Stephan ; Kienzer, Michael ; Koopmann, Jörg ; Korpys, Andree ; Löffler, Markus ; M+M ; Maier Neustadt, Hermann ; Neusser, Peter ; Radermacher, Norbert ; Roth, Daniel ; Smigla-Bobinski, Karina ; Stalker ; Stollsteiner, Mariott
biog., ind. tent., gr. tent. p. 82-92
Duits
Exhibition. Impark : Aktuelle Kunst im Olympiapark München, 18.07.2003 - 12.10.2003.
boek
Keywords: München